A Novel Application of Hydrotropic Solubilization in the Analysis of Bulk Samples of Ketoprofen and Salicylic Acid - Maheshwari, R.K. (Asian Journal of Chemistry, 2010)
In the present investigation, hydrotropic solubilization technique has been employed to solubilize the poorly water soluble antiinflammatory drug, ketoprofen (by 2.0 M sodium benzoate, 2.0 M sodium salicylate and 2.0 M sodium acetate solutions) and the poorly water soluble keratolytic drug, salicylic acid (by 2.0 M sodium benzoate, 8.0 M urea and 1.25 M sodium citrate solutions) for their titrimetric analyses The proposed method is new, simple, accurate and reproducible. Statistical data prove the accuracy, reproducibility and precision of the proposed method.